Islamisasi Ilmu Ekonomi Analisa Komparatif Kurikulum Jurusan SMI IAIN Ar-Raniry dan Jurusan Ekonomi IIUM - Hafas Furqani (Share: Jurnal Ekonomi dan Keuangan Islam, 2012)
There is a growing trend in the Muslim world to restructure modern knowledge and discipline in line with Islamic epistemological principles. Islamic economics, in particular, receives wide attention among scholars. Islamic economics is currently moving from a mere discourse on economics in Islamic perspective towards becoming a distinct discipline marked by a complete body of knowledge, clear subject matter, methodology/methodologies to appraise theories and continuous grow of knowledge. At the practical level, the universities all around the world are offering various subjects on Islamic economics and finance. There are significant attempts have been made to structure new framework of economics curriculum by incorporating various discipline of Islamic economics. The paper attempts to observe and survey the Islamization of knowledge program at the International Islamic University Malaysia and IAIN Ar-Raniry Banda Aceh Indonesia. A comparative analysis on the teachings and syllabus of Islamic economics, banking and finance in both universities will be made. Some recommendations on the structure and program of Islamic economics at IAIN Ar-Raniry which is going to be officiated as Islamic University will also be outlined. ABSTRAK - Saat ini sedang berkembang tren di dunia muslim untuk merestrukturisasi pengetahuan modern dan disiplin sesuai dengan prinsip epistemologis Islam. Ekonomi Islam, khususnya, mendapatkan perhatian luas di kalangan ilmuwan. Ekonomi Islam saat ini bergerak dari sekadar wacana tentang ekonomi dalam perspektif Islam menjadi disiplin yang berbeda ditandai dengan tubuh pengetahuan yang lengkap, materi pelajaran yang jelas, metodologi untuk menilai teori dan pengetahuan yang tumbuh secara terus-menerus. Pada tingkat praktis, saat ini universitas di seluruh dunia saat ini menawarkan berbagai mata pelajaran ekonomi dan keuangan Islam. Ada upaya-upaya signifikan yang telah dilakukan untuk membangun kerangka kerja baru kurikulum ekonomi dengan memasukkan berbagai disiplin ilmu ekonomi Islam. Makalah ini mencoba untuk mengamati dan menyurvei Islamisasi program pengetahuan pada International Islamic University Malaysia dan IAIN Ar-Raniry Banda Aceh Indonesia. Sebuah analisis komparatif pada ajaran-ajaran dan silabus ekonomi Islam, perbankan dan keuangan di kedua universitas akan dibuat. Beberapa rekomendasi tentang struktur dan program ekonomi Islam di IAIN Ar-Raniry yang akan diresmikan sebagai Universitas Islam juga akan diuraikan.